Effect of Extrinsic Motivation and Competence on Employee Performance: Study at a Credit Company in the City of Bandung - Alvin Noor Syawal; Aan Hardiyana; Nenny Rinawati; Indri Ayu Tansar (Majalah Bisnis & IPTEK, 2023)
This study aims to determine the Effect of Extrinsic Motivation and Competence on Employee Performance in the Indonesian Credit Guarantee General Companies Bandung Branch Office by obtaining accurate data and collecting the necessary data as analysis material. The purpose of this study is to determine the magnitude of the influence of extrinsic motivation, the magnitude of the influence of competence on employee performance, and the magnitude of the influence of extrinsic motivation and competence on employee performance at the Indonesian Credit Guarantee General Company Bandung Branch Office. This study uses descriptive methods and verifiable analysis with the number of respondents 35 permanent employees (sample) from 35 permanent employees (population) at the Indonesian Credit Guarantee General Company Bandung Branch Office, with the results of this study using correlation analysis, path analysis, and coefficient of determination analysis (Kd). Its operations use SPSS software version 22, Microsoft Word 2019, and Microsoft Excel 2019. Based on the results of research that has been carried out at the Indonesian Credit Guarantee General Company, namely the extrinsic motivation to obtain reasonably good results, competence to obtain relatively good results, and performance to obtain reasonably good results. The correlation between extrinsic motivation and competence obtained a positive relationship result of 0.745. The coefficient of determination is 68.5%. The direct and indirect influence of extrinsic motivation on employee performance was 43.24%, and the influence of competence on employee performance was 30.19%, so the total effect was 73.43%, and the remaining 26.57% were other variables that also affected employee performance at the Indonesian Credit Guarantee Public Company Bandung Branch Office but were not researched.